Recent Trends in Heavy Metal Pollution of Groundwater: A Review - Sameer Bairwa; Santanu Mallik (International Journal of Environmental Noise and Pollution Control, 2026)
Heavy metal pollution in groundwater has emerged as a major environmental and public health concern worldwide due to its persistence, toxicity, and potential for bioaccumulation. Rapid industrialisation, urban expansion, intensive agriculture, mining activities, and improper waste disposal have significantly increased the release of heavy metals into subsurface environments. Groundwater, being a primary source of drinking water in many regions, is particularly vulnerable to contamination, posing serious risks to human health and ecosystem sustainability. This review synthesises recent research trends on heavy metal pollution in groundwater, with emphasis on studies published in the last decade. The review critically examines the sources, distribution, and behaviour of heavy metals in groundwater systems, highlighting both natural and anthropogenic contributions. Particular attention is given to the pathways through which heavy metals migrate from soils and sediments into aquifers and their spatial and temporal variability. The health impacts associated with chronic exposure to contaminated groundwater, including carcinogenic and non-carcinogenic risks, are also discussed. In addition, recent advances in detection, monitoring, and analytical techniques used for assessing groundwater contamination are reviewed, along with their advantages and limitations. This study further evaluates commonly adopted remediation and management strategies for controlling heavy metal pollution in groundwater, including physical, chemical, and biological approaches. Emerging treatment technologies and sustainable management practices are also highlighted. By integrating recent findings, this review identifies key research gaps, methodological limitations, and challenges in groundwater contamination assessment and management. The outcomes of this review aim to provide a comprehensive understanding of current research directions and support the development of effective strategies for mitigating heavy metal pollution in groundwater, thereby contributing to improved water resource management and public health protection.
Keywords: Heavy metals; Human health risk; Monitoring techniques; Remediation strategies; groundwater contamination